Pendampingan Pemanfaatan Legalitas NIB UMKM Quin Koi Farm Melalui Sistem Online Single Submission (OSS) di Kelurahan Pakunden - Gideon Setyo Budi Witjaksono; Shelly Muharrafa Hendinie; Adelya Putri Mahardhika; Izah Bana Murtazah; Sheni Nahla Syifani; Via Aldina Auva (Jurnal Pengabdian Kepada Masyarakat, 2024)
This research is used to know the importance of business legality, even the challenges and opportunities faced in running a business. This research was conducted from March to June 2023 which is located in Pakunden Village, Sukorejo District, Blitar City by Group 40 KKN-T MBKM Univesity of East Java "Veteran" National Development. In this community service activity, a group of 40 conducted a survey of each MSME actor and made observations to find and study information related to the work program. After that, conducting counseling to one of the Quin Koi Farm MSME actors to discuss the importance of having business legality. The importance of holding counseling and mentoring activities is used so that business actors can manage their business in a sustainable manner. These activities can be carried out by local related parties such as the cooperative, urban village, and other parties. The information technology-based licensing system used to make NIB is faster and simpler, namely through Online Single Submission (OSS).